A Case of an Obstructive Intramural Haematoma during Percutaneous Coronary Intervention Successfully Treated with Intima Microfenestrations Utilising a Cutting Balloon Inflation Technique. (19th November 2018) - Alsanjari, Osama; Myat, Aung; Cockburn, James; Karamasis, Grigoris V.; Hildick-Smith, David; Kalogeropoulos, Andreas S.
Abstract : During percutaneous coronary interventions (PCI), good lesion preparation with adequate balloon predilatation is a fundamental step before stent deployment in order to achieve optimal stent expansion and favourable long-term outcomes post PCI. During PCI, inadvertent vessel tearing can occur, resulting in coronary dissections and formation of intramural haematomas. The latter might be associated with compression of the vessel lumen and significant compromise of the coronary blood flow leading to myocardial ischaemia and infarction. Herein, we present a case of intramural haematoma that occurred after PCI of the left anterior descending artery resulting in occlusion of the vessel and the subsequent use of a cutting balloon inflation technique to resolve the haematoma and restore the normal coronary blood flow.